The relationship between agility, linear sprinting, and vertical jumping performance in U-14 and professional senior team sports players - Gisladottir, Thordis; Petrović, Miloš; Sinković, Filip; Novak, Dario (Frontiers in Sports and Active Living, 2024)
The aim of this paper is to determine the relationship between the modified agility T-test (change of direction speed ability), 20-meter sprint test (linear speed ability), and countermovement jump test (vertical jumping performance) in U-14 and professional senior team sports players.The sample included 78 (59 female and 19 male) U-14 athletes (age 11.70 ± 1.33 years, height 153.00 ± 12.20 cm and body mass 47.10 ± 11.20 kg) and 43 (18 female and 25 male) senior professional athletes (age 24.80 ± 6.58 years, height 169.00 ± 9.13 cm and body mass 71.20 ± 15.10 kg). BParticipants underwent a series of tests to assess their speed, change of direction speed, and explosive power. Pearson´s product momentcorrelation coefficient (r) served to determine correlations and linear regression was conducted to explain the relationship between the dependent variable (CODS) and independent variables (S20m and CMJ). The level of statistical significance was set at p < 0.05 and the confidence interval was 95%.The Pearson product-moment correlation analysis in the U-14 athletes indicated no correlation (r = 0.11, p = 0.34) between the 20-meter linear sprint speed and the modified change of direction T-test. Additionally, the results revealed that 4 out of 10 CMJ values showed a significant moderate correlation (r = 0.3, p < 0.05) between CMJ and the modified change of direction T-test. In contrast, senior players exhibited statistically significant correlations in all variables. A significant correlation (r = 0.90, p = 0.01) was found between 20-meter linear sprint speed and the modified change of direction T-test, while CMJ values showed a range of correlations from moderate to large. In both competitive categories, according to the linear regression model, only linear sprint speed over 20 meters significantly explained (p < 0.05) the CODS speed ability, while the other CMJ parameters did not reach the significance level (p > 0.05).The study emphasized the influence of explosive power performance (CMJ) and linear speed (S20m) on agility (CODS) within the sample, particularly among professional senior team sports players. These findings indicate that agility, linear sprinting, and jumping abilities may share common underlying factors.